O nome-do-pai em Jacques Lacan : declinações e negatividade - Marcelo Fonseca Gomes de Souza (2015)
This research aims to circumscribe the concept Name-of-the-Father serving up to it, in two complementary ways: the decline and negativity. The first term - Declination - highlights the existence, throughout Lacan's teaching, showing changes relating to the way this operator is designed, as well as a major theoretical and clinical injunctions to which these transformations respond. The second term - negativity - is extracted from a reading strategy of the Hegelian dialectic and not only marks a dimension of the concept that remains constant during the work, but also allows a reflection on the ethical goals that support the psychoanalytic practice. From this methodological approach, we define two different lines of research, structuring this thesis: (i) the first concerns the delimitation of the genesis of the concept Name-of-the-Father, and the emphasis on the centrality of this significant in the composition of Lacanian program that returns to Freud, developed especially during the decade of 1950. The Name-of-the-Father is, then, defined as a significant exception, a necessary support for the transmission of primordial and universal law of culture - the law of the prohibition of incest. It is based, moreover, on the coherence and consistency of the symbolic structure and imposes itself as the anchor point for the orientation of desire as it is -as the formula of the paternal metaphor notably formalized - in conjunction with phallic symbol. In this first declination, we relate the negativity character Name-of-the-Father with castration, that is, checking in the field of the Other, the lack of adequate representation of the sexual as well as their inability to provide a final object to desire. The clinical device thought from this conceptual plot, must have as its telos the design of a strategy aimed at precisely the subjectivity of the fault. (ii) The second axis is related to the impact from the introduction of the concept of the object in psychoanalytic theory, among which may be cited: (a) the design of the symbolic structure is incomplete and inconsistent, since, in „extime‟ limit of its regulatory scope, it can be assumed that there is a real rest, not paid by the signifier; (b) the reintroduction, into the Lacanian school, a thorough discussion on the vicissitudes of the instinctual body; (c) the intensification of the debate on the negativity in the psychoanalytic treatment, which led us toward the negativity ontology of sense and the guidance of dedicated practice to the possibility of hosting the productive experiences of indeterminacy; and (d) pluralization of the parent names, wich appears both, in one hand, from the observation of the subject created by the multiple fictions around the attempt to circumvent intrinsic loss of enjoyment of their insertion into the language, as the other hand, appears as a topological support that makes it possible to enlance joy and desire.